A Baltic amber species of the diving beetle genus Coptotomus Say, 1830 (Coleoptera: Dytiscidae: Coptotominae) - Hendrich, Lars; Balke, Michael (Zootaxa, 2020)
We provide the first report of the Nearctic diving beetle subfamily Coptotominae Van den Branden, 1885 for the Paleactic Region, based on † Coptotomus balticus sp. n. from Baltic amber. Coptotomus Say, 1830 is otherwise distributed with five extant species and one subspecies in the Nearctic Region. The new species is the smallest species of the genus and thus readily separated from the extant taxa.